Operative Atlas of Laparoscopic and Robotic Reconstructive Urology : Second Edition - Patel, Vipul R.; Ramalingam, Manickam (Springer International Publishing : Imprint: Springer, 2017)
This second edition title is the ideal reference book for residents and fellows, with step-by-step pictures and only the essential prose. The major part of Operative Atlas of Laparoscopic and Robotic Reconstructive Urology, 2 edition is illustrated with magnificent photographs and diagrams depicting every step of a particular procedure. Instruments are clearly shown and have been photographed from both outside and inside the body. Chapters demonstrate accepted laparoscopic techniques that are the new gold standard in urology. Outcome analyses show that with laparoscopy, one can achieve the same oncologic success as with open surgery but will less morbidity.
Keywords: Medicine.; Proctology.; Reproductive medicine.; Urology.; elektronické knihy; electronic books